IMPLEMENTASI AKAD WAKALAH BI AL-UJROH PADA PRODUK RENCANA SEJAHTERAH SYARIAH PLUS ASURANSI JIWA PT AXA MANDIRI DALAM PERSPEKTIF HUKUM ISLAM - Munawir Munawir; Mahbub Mahbub; Jaka Anggara (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Human needs that are increasingly increasing along with the development of science and technology encourage people to fulfill their needs. In addition to basic needs that must be met, people also begin to protect themselves, both life protection, health protection and others. One of the PT that is engaged in protection/life insurance is PT AXA Mandiri. One of the products at AXA Mandiri is the sharia plus welfare plan product. In its implementation, the product of the sharia plus welfare plan uses the wakalah bi AL-Ujroh contract. Therefore, the purpose of this study is to determine whether the implementation of the sharia plus welfare plan product that uses the wakalah bi Al-Ujroh contract in the perspective of Islamic law is appropriate or not. This research uses library research method. The results of this study indicate that the application of the Wakalah Al-Ujroh contract in the sharia welfare plan product plus is in accordance with the contract stipulated by DSN-MUI NO: 52/DSN-MUI/III/2006. In its implementation, the Wakalah Al-Ujroh contract allows the insurance party to request ujrah from policy participants and policy participants can also authorize the insurer to manage their contribution funds. The Syariah Prosperity Plan Plus product applies the Wakalah bi Al-Ujroh contract together with the Ijarah contract because the services performed by PT AXA Mandiri are managing customer contribution funds and in accordance with Islamic law.